2019
DOI: 10.1002/jcb.29018
|View full text |Cite
|
Sign up to set email alerts
|

Leukemia‐derived exosomes: Bringing oncogenic signals to blood cells

Abstract: Leukemia is a cancer, which is derived from leukocytes and precursors of leukocytes in the bone marrow. A large number of pivotal biological processes are linked to leukemia pathogenesis. More insights into these mechanisms can provide a better developing pharmacological platform for patients with leukemia. Among the different players in leukemia pathogenesis, exosomes have appeared as a new biological vehicle, which can transfer oncogenic signals to blood cells. Exosomes are nano‐carriers, which enable transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 112 publications
(198 reference statements)
0
7
0
Order By: Relevance
“…Moreover, exosomes have also been isolated from leukemic cells and can be utilized as prognostic, diagnostic and therapeutic biomarkers in different hematologic neoplasms, such as acute myeloid leukemia, multiple myeloma and chronic lymphocytic leukemia. [71][72][73][74] Microvesicles released by the K562 cell line have been reported to contain both BCR-ABL1 DNA and transcript and are able to induce the CML phenotype in transplanted rats, or can activate BM mesenchymal stem cells promoting leukemic cells proliferation. 75,76 Few data are available on the identification and quantification of BCR-ABL1 in exosomes from CML patients, generally isolated from PB.…”
Section: Bcr-abl1 Transcript Monitoring By Digital Pcr (Dpcr)mentioning
confidence: 99%
“…Moreover, exosomes have also been isolated from leukemic cells and can be utilized as prognostic, diagnostic and therapeutic biomarkers in different hematologic neoplasms, such as acute myeloid leukemia, multiple myeloma and chronic lymphocytic leukemia. [71][72][73][74] Microvesicles released by the K562 cell line have been reported to contain both BCR-ABL1 DNA and transcript and are able to induce the CML phenotype in transplanted rats, or can activate BM mesenchymal stem cells promoting leukemic cells proliferation. 75,76 Few data are available on the identification and quantification of BCR-ABL1 in exosomes from CML patients, generally isolated from PB.…”
Section: Bcr-abl1 Transcript Monitoring By Digital Pcr (Dpcr)mentioning
confidence: 99%
“…However, certain groups have revealed that exosomes isolated from cell line cultures modulate the crosstalk between leukemia cells and the bone marrow (BM) microenvironment, and that they also carry molecular tumor markers (21)(22)(23)(24). Moreover, recent studies have indicated that leukemia-derived exosomes can be utilized as prognostic (25), diagnostic (26) and therapeutic biomarkers (27) for individuals suffering from different hematologic malignancies, such as acute myeloid leukemia (28)(29)(30), multiple myeloma (31) and chronic lymphocytic leukemia (32).…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes, as biological vehicles, could participate in the regulation of leukemia by transferring oncogenic signals to blood cells (24). Exosomal long non-coding RNAs (lncRNAs) could act as potential targets for the detection of different types of cancer (25).…”
Section: Discussionmentioning
confidence: 99%